Pendampingan Kemampuan Reading dalam Konteks Sains pada Komunitas Membaca Mahasiswa Kota Palangka Raya - Qomariah, Zaitun; Yuliani, Hamda; Hamid, Faisha Hamdan Syakirin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The community service activity is a mentoring program for student reading communities to provide reading skills in the context of science. This activity was carried out with student reading communities from various universities in Palangka Raya City for three weeks with the IAIN Palangka Raya service team. The purpose of this community service activity is to train reading skills in English and also to increase the insight of students into the science. The method of this activity includes the preparation phase (problem identification and planning), the implementation phase, and the evaluation phase (interviews and feedback). From the results of this mentoring activity, it can be concluded that this activity has a positive impact on community members by making them more productive in reading and increasing their skills and interest in reading.